Evaluation of the Intestinal Absorption Mechanism of Casearin X in Caco-2 Cells with Modified Carboxylesterase Activity - Silva, Rodrigo Moreira da; Verjee, Sheela; Gaitani, Cristiane Masetto de; Moraes de Oliveira, Anderson Rodrigo; Pires Bueno, Paula Carolina [UNESP]; Cavalheiro, Alberto Jose [UNESP]; Lopes, Norberto Peporine; Butterweck, Veronika (Amer Chemical Soc, 2016)
The clerodane diterpene casearin X (1), isolated from the leaves of Casearia sylvestris, is a potential new drug candidate due to its potent in vitro cytotoxic activity. In this work, the intestinal absorption mechanism of 1 was evaluated using Caco-2 cells with and without active carboxylesterases (CES). An LC-MS method was developed and validated for the quantification of 1. The estimation of permeability coefficients was possible only under CES-inhibited conditions in which 1 is able to cross the Caco-2 cell monolayer. The mechanism is probably by active transport, with no significant efflux, but with a high retention of the compound inside the cells. The enzymatic hydrolysis assay demonstrates the susceptibility of 1 to first-pass metabolism as substrate for specific CES expressed in human intestine.